(3EfTGA GdOhGFQs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdEfSGf ai UhQJg CeG HYO aEf Gddg SHMGfg hJYGdi deG YQafi MbGFb GdCTjGA Ydi eGgi Ydjg ai PhGJgG s
(3BNQgG (B:s
(3aJMbb gPG GdaUd GdeNJUQ GdYLjH aEfg fGaY GdHGH hGddg CYde HGdUhGH hEdjg GdeQLY hGdeBH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B9s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B281s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI eMeO CMeO GdeMGei (B_ (3GdHUQI (B(219 (3N(B) s
Keywords: (3GdeLGejYs